Hubungan Antara Kelelahan Dengan Tingkat Kecemasan Perawat Rumah Sakit: Sebuah Tinjauan Pustaka - Josafat Pondang; Kosasih Kosasih (CV. Ulil Albab Corp, 2024)
Fatigue can be caused by overwork, prolonged physical and mental activity, lack of rest, high stress or a combination of these factors. Work fatigue is caused by tiring and energy-draining activities, thereby reducing human alertness and response to stress. Anxiety is a common emotional disorder characterized by deep and persistent fear or worry, but without any disturbance in the assessment of reality. A nurse is someone who has graduated from a nursing school, both inside and outside of school, in accordance with the provisions of applicable laws and regulations. This article provides an explanation of work fatigue, anxiety and determines the relationship between anxiety and work fatigue specifically for nurses who work in hospitals. This research uses a qualitative approach research methodology by collecting data using structured interviews with 2 research subjects, namely nurses in the Emergency Department and Inpatient Installation who work in private hospitals in Wonogiri Regency accompanied by a literature review based on the literature. Based on literature sources, it was found that high work fatigue can cause an increased risk of anxiety disorders up to 2.7 times higher compared to subjects with lower work fatigue. From the results of interviews with the 2 research subjects, it was found that the level of work fatigue was positively related to anxiety, meaning that the higher the level of work fatigue based on the scoring of the Job Fatigue Measuring Tool Questionnaire (KAUPK2), the higher the anxiety level score based on the Hamilton Anxiety Rating Scale.